Benzoxaborole-grafted high molecular weight chitosan from prawn: Synthesis, characterization, target recognition and antibacterial properties - García Cambón, Tomás Agustín (2023)
Boronated polymers are in the focus of dynamic functional materials due to the versatility of the B-O interactions and accessibility of precursors. Polysaccharides are highly biocompatible, and therefore, an attractive platform for anchoring boronic acid groups for further bioconjugation of cis-diol containing molecules. We report for the first time the introduction of benzoxaborole by amidation of the amino groups of chitosan improving solubility and introducing cis-diol recognition at physiological pH. The chemical structures and physical properties of the novel chitosan-benzoxaborole (CS-Bx) as well as two phenylboronic derivatives synthesized for comparison, were characterized by nuclear magnetic resonance (NMR), infrared spectroscopy (FTIR), thermogravimetric analysis (TGA), dynamic light scattering (DLS), rheology and optical spectroscopic methods. The novel benzoxaborole grafted chitosan was perfectly solubilized in an aqueous buffer at physiological pH, extending the possibilities of boronated materials derived from polysaccharides. The dynamic covalent interaction between boronated chitosan and model affinity ligands, was studied by means of spectroscopy methods. A glycopolymer derived from poly(isobutylene-alt-anhydride) was also synthesized to study the formation of dynamic assemblies with benzoxaborole-grafted chitosan. A first approximation to apply fluorescence microscale thermophoresis for the interactions of the modified polysaccharide is also discussed. Additionally, the activity of CSBx against bacterial adhesion was studied.